Identity construction and culture reproduction among Iraya Mangyans educational and cultural process - Bawagan, Aleli B.; Abuso, Julian E.; Castro, Nestor T.; Ganaden, Mildred S.; Koo, Grace S.; Manalili, Angelito T. (2008)
The research focuses on the Iraya Mangyan's construction of their identity across generations, the forms of reproduction of their culture and identity, and the difference between Iraya men and women with respect to identify construction and culture reproduction. The findings showed that identity construction and culture reproduction are indeed both educational and cultural processes. The Iraya Mangyan identity is generally a combination of the primordial and transactional elements. The traditional methods include story-telling, observance of village traditions, rituals and costumary laws, informal community-based education systems and magic. Modern methods include formal education, presence of other institutions, advocacy, mass media and other audio-visual and literary tools. Gender has no significant effect in identity construction and culture reproduction.
"March 2008."
Research project funded by the University of the Philippines through the Office of the Vice-Chancellor for Research and Development (OVCRD).
Thesis (Ph.D. Anthropology/Sociology of Education)--University of the Philippines Diliman.
Best dissertation.
Keywords: Group identity -- Philippines -- Mindoro; Community development -- Philippines -- Mindoro; Indigenous people -- Philippines -- Mindoro